CONSTRUCTION OF FOUNDATIONS IN GRUNTS WITH VARIABLE STRUCTURES - Bakhromov Mahmud Mamatkhanovich (Journals Park Publishing, 2022)
The relevance of the topic, the significance of geological exploration work, the significance of the construction of pile foundations in such conditions, the features of foamy and salty grunts, empty grunts saturated with water, tasks in the construction of foundations in such complex conditions.
Keywords: grunt, foundation, geology, pile foundations, foaming grunts, saltwater grunts.